On human rights in Helio Gallardo's thought: praxis of liberation, social fabrics and multi-guarantees - Sánchez Rubio , David (2023)
This paper analyzes some of the contributions of Helio Gallardo’s thinking on human rights. Starting from the fundamentalproblem that human rights present, referring to the distance and the abyss that exists between their discourses, their theories and their practices, between what is said and what is done, we reflect on their social proposal. materialist based on the processes of struggle and the experiences of contrasts of modern social organizations and their social movements in the face of the deficiencies and systems of domination of the bourgeois and capitalist order. After a description of his analyzes of social struggles and liberation praxis, a multiguarantor system of human rights is proposed that revolves around individual and collective practices and actions that display a reality of them based on a culture that he conceives them multidimensionally full time and everywhere.